Peran Kanal Cek Fakta Liputan6.Com Dalam Mengurangi Ketidakpastian Informasi - Rachman, Adrian Gevita; Poerana, Ana Fitirana; Teguh, Made Panji (CV. ITTC INDONESIA, 2024)
Fact Checking Journalism is an important activity in tackling hoaxes in digital media. Liputan6.com is one of the online media that has a Fact Check Channel verified by the International Fact Checking Network (IFCN). This research examines the fact-checking procedures carried out by the Liputan6.com Fact Check Channel with the aim of understanding their efforts in dealing with hoaxes on digital media. The research method used is qualitative with a case study approach. The research results show that the Liputan6.com Fact Check Channel has an important role in reducing cognitive and behavioral uncertainty in society due to hoax information on digital media. They try to verify information, create Debunking articles to reveal facts from hoaxes, as well as Prebunking articles to provide education to prevent the spread of hoaxes. In conclusion, Liputan6.com is active in maintaining the truth of information and contributing to overcoming hoaxes in the digital era.